Study of solar inclination through the use of a Heliodon of removable parts for the design of the shadow of architectural elements - Montoya Torres, Vladimir Simón (2024)
The research focuses on analyzing the path of the sun around the architectural elements based on solar alignments, the objective was the manufacture of a Heliodon of removable parts which through digital manufacturing can be replicated in any FAB LAB and through this tool analyze the strokes that are generated by the shadow of architectural elements under the presence of the sun, these analyzes can be developed in the design workshops, allowing the student to better understand the changes in the inclination of the sun in its annual journey, taking into account that these inclinations They change according to latitude, longitude and solar geometry. As a conclusion of this research, Heliodon was patented in 2021 before INDECOPI, and its application in the analysis of the shadow cast could be demonstrated through the design and construction of urban panels in the year 2022 which cast a favorable shadow during times of high solar presence, currently efforts are being made to improve the learning conditions of the solar path in relation to architectural solids and their shadow, such as in high Andean areas in which efforts are being made to improve the conditions of greater thermal gain due to solar presence.